Ghostwalk : a novel - Stott, Rebecca (New York : Spiegel & Grau, 2008)
In 2002, a Cambridge historian is found dead, floating down the river Cam, a glass prism in her hand, after researching a book about a series of suspicious circumstances surrounding Newton's appointment as a Fellow of Trinity College, Cambridge, in 1667. That year, two Fellows died by falling down staircases, apparently drunk; another died in a field, apparently drunk; and a fourth was expelled, having gone mad -- leaving vacancies for new appointments and paving the way for Newton's extraordinary scientific discoveries. When Lydia Brooke, at the request of her ex-lover, the historian's son, steps in to finish the book, strange shows of light begin to play on the walls, and papers disappear only to reappear elsewhere. And when events escalate to murder, and Lydia's rekindled romance appears increasingly implicated in the danger, the present becomes entangled with the seventeenth century, with Isaac Newton at the center of the mystery.
Includes bibliographical references.
Keywords: College teachers -- Fiction; Detective and mystery fiction